Speech acts in English classroom: A case at a junior high school in Indonesia - Didin Nuruddin Hidayat; Fadhilah Fadhilah; Yudi Septiawan (EduLite: Journal of English Education, Literature and Culture, 2022)
Teachers’ speech acts play a distinct role in teaching-learning in the English as a Foreign Language (EFL) classroom. The teacher transfers knowledge to the students and becomes a role model in students’ interaction. This study aims to classify the kinds of representative speech acts expressed by teachers and students of the eighth grade at a junior high school in Indonesia. This discourse study implements a qualitative method using the observation technique. Collected from a natural pedagogical activity in the EFL classroom, the utterances were compared and analysed descriptively. The study revealed three speech acts: locution, illocution, and perlocution. Questioning and commanding adopted in 113 instances show that the teacher is aware of her/his role and has a higher position than the students. Moreover, speech acts impact EFL class, and they influence students' motivation and confidence in learning English through expressive and declarative speech acts.